International Coercion and the Diffusion of Regulatory Data Protection. (18th January 2016) - Michael, Gabriel J.
Abstract : Prior to 1990, regulatory data protection existed only in 14 highly developed countries. Since then, 60 additional countries have adopted regulatory data protection. New adopters include a large number of countries with no domestic pharmaceutical industry. These countries will face higher pharmaceutical prices as a result of offering regulatory data protection. Why would countries that stand to lose from offering regulatory data protection choose to do so? The author argues that the global diffusion of regulatory data protection can be directly traced to international coercion from the United States and the European Union (EU). The US coerces weaker trading partners into adopting regulatory data protection by requiring such protection as a condition of concluding trade agreements or bilateral intellectual property agreements. Meanwhile, the EU coerces applicants by demanding that they adopt such rights during EU accession negotiations, on average four years prior to accession. He tested these claims using a multi‐method research design that combines event history analysis with evidence from leaked US diplomatic cables and public EU accession documents. His findings demonstrate that coercive diffusion can take place by means of threats, and that countries often actively oppose adopting intellectual property rights, but nevertheless adopt them due to international coercion.